Controversies in complex percutaneous coronary intervention: radial versus femoral. (2nd September 2017) - Gilchrist, Ian C.; Awuor, Stephen O.; Davies, Rhian E.; Ukaigwe, Anene C.
ABSTRACT: Introduction : Evolution in the technology used in the cardiac catheterization laboratory has permitted a migration from the femoral to radial artery access for many interventional procedures while concurrently improving outcomes. As a disruptive technology, transradial access has been associated with several controversies including a dichotomous relationship with femoral access. Areas covered : Several different patient subsets along with perceived technical challenges in interventional cardiology are reviewed with regard to the issue of access site. Evolving technological improvements germane to transradial techniques are also discussed as garnered from the literature of recent clinical trials and reports. Expert commentary : Radial techniques have been enhanced by newer technology and the spread of knowledge. Fusion of radial techniques with those of the femoral approach is evolving into a unifying concept of using the access that is most appropriate for the patient. No one access technique can cover all clinical subsets of patients. There is a need for complimentary access skillsets for even the most advanced cardiovascular technology used in the cardiac catheterization laboratory if the patients' outcomes are to be idealized.